2009
DOI: 10.14310/horm.2002.1226
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-associated adverse events

Abstract: The adverse events of the nitrogen-containing bisphosphonates are reviewed. Oral bisphosphonates (alendronate, risedronate and ibandronate), mainly used for the treatment of osteoporosis, have been associated with adverse events from the upper gastrointestinal tract, acute phase response, hypocalcaemia and secondary hyperparathyroidism, musculoskeletal pain, osteonecrosis of the jaw and ocular events. Intravenous bisphosphonates (pamidronate, ibandronate and zoledronic acid), used in oncology and for the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
174
2
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(196 citation statements)
references
References 102 publications
2
174
2
9
Order By: Relevance
“…1,68,69 Despite the evidence that BTAs provide a significant clinical benefit for patients with BM, these drugs are also responsible Bone remodeling markers in bone metastatic disease A Ferreira et al for relevant adverse events, such as hypocalcemia or osteonecrosis of the jaw. 71 Moreover, the rate of adverse events associated with BP treatment increases with time, 71 and only limited evidence assessed long-term use of BPs. 12,71 Given the prompt response of bone markers to treatment with BTAs and their use as predictors of BTAs efficacy (particularly with ZA), some authors hypothesized that the serial measurement of bone markers could be a strategy to tailor therapy regimen.…”
Section: Dosing Of Btasmentioning
confidence: 99%
See 1 more Smart Citation
“…1,68,69 Despite the evidence that BTAs provide a significant clinical benefit for patients with BM, these drugs are also responsible Bone remodeling markers in bone metastatic disease A Ferreira et al for relevant adverse events, such as hypocalcemia or osteonecrosis of the jaw. 71 Moreover, the rate of adverse events associated with BP treatment increases with time, 71 and only limited evidence assessed long-term use of BPs. 12,71 Given the prompt response of bone markers to treatment with BTAs and their use as predictors of BTAs efficacy (particularly with ZA), some authors hypothesized that the serial measurement of bone markers could be a strategy to tailor therapy regimen.…”
Section: Dosing Of Btasmentioning
confidence: 99%
“…71 Moreover, the rate of adverse events associated with BP treatment increases with time, 71 and only limited evidence assessed long-term use of BPs. 12,71 Given the prompt response of bone markers to treatment with BTAs and their use as predictors of BTAs efficacy (particularly with ZA), some authors hypothesized that the serial measurement of bone markers could be a strategy to tailor therapy regimen. Actually, the serial measurements of these markers could allow changing treatment frequency (for example, every 3 months) and even theoretically allow removing therapy for periods in the context of optimal bone metabolism control.…”
Section: Dosing Of Btasmentioning
confidence: 99%
“…No difference in renal function was observed between patients receiving risedronate or placebo in any of the renal impairment subgroups at any point during this study. In the pooled analysis of risedronate treatment the incidence of new vertebral fractures in the placebo groups was significantly correlated with the severity of renal function; however, BF treatment significantly reduced this incidence compared to placebo within each category of renal impairment [16].…”
Section: Introductionmentioning
confidence: 87%
“…Miller [16] showed that, a daily 5 mg dose of risedronate over an average of 2 years did not significantly change serum creatinine concentration. No difference in renal function was observed between patients receiving risedronate or placebo in any of the renal impairment subgroups at any point during this study.…”
Section: Introductionmentioning
confidence: 99%
“…그러나 Bisphosphonate 제제는 부작용이 많으며, 소수의 환자들에게는 심각한 부작용을 일으키고 있다. 즉, 급성기 반응, 근골격 의 심한 고통, 저칼슘혈증 등의 단기부작용부터 턱뼈 부 분의 뼈괴사증, 심방세동, 심한 뼈교체억제 등의 장기부 작용까지 다양한 부작용을 일으켜 때때로 매우 치명적 이다 [15,16]. 이에 따라 부작용이 적으면서도 골다공증 치료 및 예방에 효과적인 신물질을 찾는 연구가 활발히 진행되고 있다.…”
unclassified